2010
DOI: 10.4317/medoral.15.e639
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial pain associated to trigger points: A literature review. Part 2: Differential diagnosis and treatment

Abstract: During the last decades the advance in knowledge of myofascial pain has been constant in the medical and dental community. However, although several aspects have been clarified in relation to its epidemiology, clinical characteristics and etiopathogenesis, many uncertainties remain. Many clinical conditions are included in the differential diagnosis of myofascial pain associated to trigger points. A good anamnesis and clinical exploration is thus required in order to ensure correct diagnosis and treatment. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
(43 reference statements)
0
12
0
6
Order By: Relevance
“…Un año más tarde, Majlesi y Unalan 28 proponen como modalidades terapéuticas eficaces el calor local y frío, ejercicios de estiramiento, espray y estiramiento, punción, inyección local, y US. Ese mismo año, Vázquez-Delgado y col 29 exponen que la técnica de espray y estiramiento y la inyección en el PGM son las opciones más eficaces; además se destaca que en casos crónicos, se requiere de intervención psicosocial por los trastornos de ansiedad observados.…”
Section: Síndrome De Dolor Miofascial Cervical Y Su Abordaje Fisioterunclassified
See 1 more Smart Citation
“…Un año más tarde, Majlesi y Unalan 28 proponen como modalidades terapéuticas eficaces el calor local y frío, ejercicios de estiramiento, espray y estiramiento, punción, inyección local, y US. Ese mismo año, Vázquez-Delgado y col 29 exponen que la técnica de espray y estiramiento y la inyección en el PGM son las opciones más eficaces; además se destaca que en casos crónicos, se requiere de intervención psicosocial por los trastornos de ansiedad observados.…”
Section: Síndrome De Dolor Miofascial Cervical Y Su Abordaje Fisioterunclassified
“…Según muestra una revisión reciente la terapia manual se ha considerado como el conjunto de técnicas más eficaces en la inactivación de PGM 33 . Diversos estudios y revisiones previamente citados 19,[25][26][27][28][29][30] defienden el beneficio que aportan dichas técnicas, aunque ciertamente, la terapia manual es difícil de valorar debido a la variabilidad de aplicación por el fisioterapeuta y por la propia reacción e idiosincrasia de cada paciente.…”
Section: Terapia Manualunclassified
“…18) A review suggested 0.5% as the ideal concentration of local anesthetics after considering the therapeutic advantages. 24) Other studies have reported that the most effective concentration for local anesthetics ranged between 0.2% and 0.25% rather than 1%. 34,35) Regarding additive use with local anesthetics, any additives including vasoconstrictors and bisulfite should not be included because they cause post-injection sensitivity and pain.…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…34,35) Regarding additive use with local anesthetics, any additives including vasoconstrictors and bisulfite should not be included because they cause post-injection sensitivity and pain. 24) Regarding the additional effects of injectates, many studies have shown no significant differences among groups of dry needling and wet needling using steroid, procaine or lidocaine, and botulinum toxin. 23,36,37) These findings implied that the main mechanism of the analgesic action of dry needling and even injection might be the disruption of comfort.…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…Invasive techniques include acupuncture and botulin injections, whereas non-invasive ones include joint manipulation, tension/relaxation, ischemic compression, transverse friction massage, post-isometric relaxation [14], spray and stretch [17,18], kinesio taping [19], transcutaneous electrical nerve stimulation, ultrasound, and lasers. Despite the abundance of MTP treatment techniques, manual therapy remains one of the main approaches, and the role of physical therapist in the treatment of MTP should not be underestimated [14].…”
mentioning
confidence: 99%